Speech Image of German Politicians as an Expression of Language Picture of the World. - A. P. Kryachkova (Vestnik MGIMO-Universiteta)
The purpose of the article is to give a general notion of the meanings “language picture of the world” and “speech image” and identify the relationship of these meanings in cultural linguistics. The author describes German language picture of the world and its development in German politicians’ speech image.